Balance Impairment in Fahr’s Disease: Mixed Signs of Parkinsonism and Cerebellar Disorder. A Case Study - Scarano, Stefano; Rota, Viviana; Tesio, Luigi; Perucca, Laura; Robecchi Majnardi, Antonio; Caronni, Antonio (Frontiers in Human Neuroscience, 2022)
Fahr’s disease is a rare idiopathic degenerative disease characterized by calcifications in the brain, and has also been associated with balance impairment. However, a detailed analysis of balance in these patients has not been performed. A 69-year-old woman with Fahr’s disease presented with a long-lasting subjective imbalance. Balance was analyzed using both clinical (EquiScale, Timed Up and Go test, and Dizziness Handicap Inventory-short form) and instrumented tests (the sway of the body center of mass during quiet, perturbed, and self-perturbed stance, and the peak curvature of the center of mass during single stance while walking on a force-treadmill). The patient’s balance was normal during clinical tests and walking. However, during standing, a striking impairment in vestibular control of balance emerged. The balance behavior displayed mixed parkinsonian (e.g., slowness and reduced amplitude of movement) and cerebellar (e.g., increased sway during standing in all conditions and decomposition of movement) features, with a discrepancy between the high severity of the static and the low severity of the dynamic balance impairment. The balance impairment characteristics outlined in this study could help neurologists and physiatrists detect, stage, and treat this rare condition.